(untitled) (Ágora Journal, 2020)
The Sociedade Protetora dos Desvalidos, Brazil’s first black civil association, installed in 1851 in the city of Salvador, became an important space for negotiation between color leaders and Bahian politicians in the second half of the 19th century. Some of its associates stood out as important leaders and achieved a status of enormous prestige among the colored workers of the city of Salvador. This article aims to understand the meanings of the articulations of these leaders with important figures from Bahia. It seeks to investigate how those workers, mostly artists and craftsmen, negotiated and disputed a political project for men of color, with the intention of achieving basic rights as citizens, such as education, dignity, mutual assistance, political participation and racial belonging.